Factors Influencing Food Choice for Independently Living Older People—A Systematic Literature Review. Issue 2 (2nd April 2016) - Host, Alison; McMahon, Anne-Therese; Walton, Karen; Charlton, Karen
ABSTRACT: Unyielding, disproportionate growth in the 65 years and older age group has precipitated serious concern about the propensity of health and aged-care services to cope in the very near future. Preservation of health and independence for as long as possible into later life will be necessary to attenuate demand for such services. Maintenance of nutritional status is acknowledged as fundamental for achievement of this aim. Determinants of food choice within this age group need to be identified and better understood to facilitate the development of pertinent strategies for encouraging nutritional intakes supportive of optimal health. A systematic review of the literature consistent with PRISMA guidelines was performed to identify articles investigating influences on food choice among older people. Articles were limited to those published between 1996 and 2014 and to studies conducted within countries where the dominant cultural, political and economic situations were comparable to those in Australia. Twenty-four articles were identified and subjected to qualitative analysis. Several themes were revealed and grouped into three broad domains: (i) changes associated with ageing; (ii) psychosocial aspects; and (iii) personal resources. Food choice among older people is determined by a complex interaction between multiple factors. Findings suggest the need for further investigations involving larger, more demographically diverse samples of participants, with the inclusion of a direct observational component in the study design.